Overview of Covid-19 Countermeasures through Village Revenue and Spending Budget in East Kalimantan - Kusuma, Aji Ratna; Awaluddin, Muhammad (Budapest International Research and Critics University, 2021)
The focus of this study includes refocusing APBDesa in 2020, prevention of the spread or transmission of Covid-19 in the village, and the handling of people who are symptomatic of Covid-19. This study was conducted in East Kalimantan Province with 10 regencies that became a population consisting of three cities and seven districts. This research uses secondary data and primary data of interview results in the form of qualitative so that the type of research used is qualitative research that is Case Study and Narrative. Qualitative data from interviews was analyzed using Nvivo 12 analysis. The results of this study are refocusing the Village Revenue and Spending Budget through a mechanism based on tiered policies from the Central Government, Provincial Government and District Government through regulations that are comprehensive to all regions so that in its implementation the village has a clear legal basis and can be accounted for. A rapid and precise re-focusing policy has succeeded in inhibiting the spread of covid-19 in villages characterized by low cases of exposure and cases of death in villages except villages that are on the outskirts of the city.